2006
DOI: 10.1088/0953-8984/18/26/012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation spectroscopy study of the effects of growth interruptions on the interfaces of GaAsSb/GaAs multiple quantum wells

Abstract: The effects of growth interruption times combined with Sb exposure of GaAsSb/GaAs multiple quantum wells (MQWs) have been investigated by using phototransmittance (PT), contactless electroreflectance (CER) and wavelength modulated surface photovoltage spectroscopy (WMSPS). The features originated from different portions of the samples, including interband transitions of MQWs, interfaces and GaAs, are observed and identified through a detailed comparison of the obtained spectra and theoretical calculation. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In contrast to conventional III-III'-V alloy systems such as AlGaAs, strong competition between two group-V elements in GaAsSb leads to their non-unity sticking coefficients, which complicates the incorporation behavior of Sb and As atoms. 10,11 It was shown that a naturally formed Sb gradients exists in GaAsSb epitaxial layers grown by molecular beam epitaxy (MBE). 12 Moreover, a consistent self-induced Sb compositional gradients are also observed in GaAsSb nanowires grown by MBE, leading to a specific and reproducible rectifying behavior.…”
mentioning
confidence: 99%
“…In contrast to conventional III-III'-V alloy systems such as AlGaAs, strong competition between two group-V elements in GaAsSb leads to their non-unity sticking coefficients, which complicates the incorporation behavior of Sb and As atoms. 10,11 It was shown that a naturally formed Sb gradients exists in GaAsSb epitaxial layers grown by molecular beam epitaxy (MBE). 12 Moreover, a consistent self-induced Sb compositional gradients are also observed in GaAsSb nanowires grown by MBE, leading to a specific and reproducible rectifying behavior.…”
mentioning
confidence: 99%
“…The period of FKO is known to be strongly related to the built-in electric field of semiconductors and their heterostructures. The electric field is proportional to the period of FKO [10]. However, in this structure, we cannot expect any built-in electric field because these structures are composed of only undoped layers.…”
Section: Methodsmentioning
confidence: 93%
“…To reduce the compositional gradient not only at the start of the Sb layer but also at the final interface, different growth approaches have been proposed. On the one hand, applying different growth interruption (GI) times with Sb exposure ("soaking") prior to the growth of a new Sb-containing layer has been associated with better structural quality and higher Sb incorporation [18][19][20], which leads to better optical performances [21,22]. In general, antimonides present weaker bonds compared to arsenides, so the As-for-Sb exchange is energetically favorable, leading to slower incorporation of Sb atoms into epitaxies with simultaneous As deposition [23].…”
Section: Introductionmentioning
confidence: 99%